Phytoextraction efficiency of Arabidopsis halleri is driven by the plant and not by soil metal concentration. (December 2021) - Dietrich, Charlotte C.; Tandy, Susan; Murawska-Wlodarczyk, Kamila; Banaś, Angelika; Korzeniak, Urszula; Seget, Barbara; Babst-Kostecka, Alicja
Abstract: The hyperaccumulation trait allows some plant species to allocate remarkable amounts of trace metal elements (TME) to their foliage without suffering from toxicity. Utilizing hyperaccumulating plants to remediate TME contaminated sites could provide a sustainable alternative to industrial approaches. A major hurdle that currently hampers this approach is the complexity of the plant-soil relationship. To better anticipate the outcome of future phytoremediation efforts, we evaluated the potential for soil metal-bioavailability to predict TME accumulation in two non-metallicolous and two metallicolous populations of the Zn/Cd hyperaccumulator Arabidopsis halleri . We also examined the relationship between a population's habitat and its phytoextraction efficiency. Total Zn and Cd concentrations were quantified in soil and plant material, and bioavailable fractions in soil were quantified via Diffusive Gradients in Thin-films (DGT). We found that shoot TME accumulation varied independent from both total and bioavailable soil TME concentrations in metallicolous individuals. In fact, hyperaccumulation patterns appear more plant- and less soil-driven: one non-metallicolous population proved to be as efficient in accumulating Zn on non-polluted soil as the metallicolous populations in their highly contaminated environment. Our findings demonstrate that in-situ information on plant phytoextraction efficiency is indispensable to optimize site-specific phytoremediation measures. If successful, hyperaccumulating plant biomass may provide valuable source material for application in the emerging field of green chemistry. Graphical abstract: Image 1 Highlights: Soil metal concentration is a poor predictor of metal accumulation in plant biomass. Non-metallicolous populations may be extraordinarily efficient metal accumulators. Metal bioaccumulation decreases non-linearly with increasing soil metal content. Depending on the population, 79′000 to 530′000 plants are needed to mine 1 kg of zinc. Plant material has to be optimized for a given site to maximize metal phytoextraction.